Chromosomal and cytoplasmic context determines predisposition to maternal age-related aneuploidy: brief overview and update on MCAK in mammalian oocytes. (24th November 2010) - Eichenlaub-Ritter, Ursula; Staubach, Nora; Trapphoff, Tom
Abstract : It has been known for more than half a century that the risk of conceiving a child with trisomy increases with advanced maternal age. However, the origin of the high susceptibility to nondisjunction of whole chromosomes and precocious separation of sister chromatids, leading to aneuploidy in aged oocytes and embryos derived from them, cannot be traced back to a single disturbance and mechanism. Instead, analysis of recombination patterns of meiotic chromosomes of spread oocytes from embryonal ovary, and of origins and exchange patterns of extra chromosomes in trisomies, as well as morphological and molecular studies of oocytes and somatic cells from young and aged females, show chromosome-specific risk patterns and cellular aberrations related to the chronological age of the female. In addition, analysis of the function of meiotic- and cell-cycle-regulating genes in oogenesis, and the study of the spindle and chromosomal status of maturing oocytes, suggest that several events contribute synergistically to errors in chromosome segregation in aged oocytes in a chromosome-specific fashion. For instance, loss of cohesion may differentially predispose chromosomes with distal or pericentromeric chiasmata to nondisjunction. Studies on expression in young and aged oocytes from human or model organisms, like the mouse, indicate that the presence and functionality/activity of gene products involved in cell-cycle regulation, spindle formation and organelle integrity may be altered in aged oocytes, thus contributing to a high risk of error in chromosome segregation in meiosis I and II. Genes that are often altered in aged mouse oocytes include MCAK (mitotic-centromere-associated protein), a microtubule depolymerase, and AURKB (Aurora kinase B), a protein of the chromosomal passenger complex that has many targets and can also phosphorylate and regulate MCAK localization and activity. Therefore we explored the role of MCAK in maturing mouse oocytes by immunofluorescence, overexpression of a MCAK–EGFP (enhanced green fluorescent protein) fusion protein, knockdown of MCAK by RNAi (RNA interference) and inhibition of AURKB. The observations suggest that MCAK is involved in spindle regulation, chromosome congression and cell-cycle control, and that reductions in mRNA and protein in a context of permissive SAC (spindle assembly checkpoint) predispose to aneuploidy. Failure to recruit MCAK to centromeres and low expression patterns, as well as disturbances in regulation of enzyme localization and activity, e.g. due to alterations in activity of AURKB, may therefore contribute to maternal age-related rises in aneuploidy in mammalian oocytes.